PERANCANGAN VIDEO PROMOSI IDENTITY HANDMADE - Irfan Yulian; syafwandi syafwandi (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
The main purpose of this design is to promote the fashion product and tailoring service that providing by Identity handmade, then hopefully can be able to increase consumer buying interest towards Identity Handmade product's. Identity Handmade promotional video design is using several theory which are video theory, promotional theory, communication theory and visual communication and design theory. Then the promotional video is got strengthened by using design method which is FOUR D method. FOUR D design method is define, design, development and disseminate. Promotional video as the major media got supported by using supporting media such as T-shirt, mask, keychain, sticker, pin, poster and social media instagram.Kata kunci: produk fashion, promosi, video, Identity Handmade.